PHOTO-SENSITIVE LAYERS FORMED FROM POLYMETHYLTHIOPHENE/TiO2NANOCOMPOSITES - Trung, Vu Quoc; Tinh, Thai Doan; Dieu, Tran Vinh; Pfleger, Jiri; Plieth, Waldfried (Vietnam Journal of Chemistry, 2014)
Nanocomposites of polymethylthiophene (PMT) and titanium dioxide nanoparticles (TiO2)were prepared in core-shell structure, via chemical oxidative polymerization of methylthiophene in the presence of FeCl3catalyst. The electrophoretic deposition (EPD) technique was adopted to prepare the nanocomposite films on ITO plates. Then photoelectrochemical properties of the PMT/TiO2nanocomposite were investigated. Results showed the photo-sensitive properties of TiO2core (n-type semiconductor), PMT shell (p-type semiconductor) and their n-p junction